2010
DOI: 10.3390/molecules16010251
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds in Brassica Vegetables

Abstract: Phenolic compounds are a large group of phytochemicals widespread in the plant kingdom. Depending on their structure they can be classified into simple phenols, phenolic acids, hydroxycinnamic acid derivatives and flavonoids. Phenolic compounds have received considerable attention for being potentially protective factors against cancer and heart diseases, in part because of their potent antioxidative properties and their ubiquity in a wide range of commonly consumed foods of plant origin. The Brassicaceae fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

37
627
0
17

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 830 publications
(747 citation statements)
references
References 108 publications
37
627
0
17
Order By: Relevance
“…High temperature of hot water might cause the destruction of some phenolic compounds. Phenolic compounds are phytochemicals abundant in plants (Cartea et al 2011). Type and amount of phenolic compounds varied with plant, maturation, season, etc.…”
Section: Effect Of Extraction Solvent On Yield Compositions and Antimentioning
confidence: 99%
“…High temperature of hot water might cause the destruction of some phenolic compounds. Phenolic compounds are phytochemicals abundant in plants (Cartea et al 2011). Type and amount of phenolic compounds varied with plant, maturation, season, etc.…”
Section: Effect Of Extraction Solvent On Yield Compositions and Antimentioning
confidence: 99%
“…Recent interest in phenolic acids stems from their potential protective role, through ingestion of fruits and vegetables, against oxidative damage diseases (coronary heart disease, stroke, and cancers). This also may be attributed to their antioxidant activity which was reported to be higher than the vitamin antioxidants (Cartea et al 2011). In view of the impact of both phenolic acids and flavonoids on human health, it is essential to learn about their amounts and varieties in medicinal plants (Bravo 1998;Scalbert and Williamson 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These factors largely affect the primary and secondary metabolism of brassica plants, resulting in the enhanced production of certain metabolites, e.g., amino acids, sugars, indoles, phenolic compounds and glucosinolates (Jacobo-Velázquez, Cisneros-Zevallos 2012). Phenolic compounds are produced in plants as secondary metabolites (Cartea et al 2011). Cheynier et al (2013) reported that plants produce an enormous number of phenolic secondary metabolites, which are of vital importance for their interaction with the environment.…”
mentioning
confidence: 99%
“…Phenolic compounds, depending on their structure, can be classified into simple phenols, phenolic acids, hydroxycinnamic acid derivatives and flavonoids (Cartea et al 2011). Brassicaceae are known to contain flavonoids (Soengas et al 2012), and especially flavonols (Pollastri, Tattini 2011;Agati et al 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation